Determining Alternative Mechanical Quality of Aluminum for Making Ordered Equipment Using the Multifactor Evaluation Process (MFEP) Method - Lony Armawati Tambunan; Rini Sovia; Wifra Safitri (Journal of Computer Scine and Information Technology, 2023)
Many various types of industrial companies use aluminum to support their industrial productivity. One of the reasons companies use this aluminum material is because aluminum is a good electrical conductor, light and strong. In determining which aluminum metal is suitable to be used to make ordering equipment, of course the metal with the best quality must be chosen so that the production of aluminum equipment is in demand by many consumers. Multi Factor Evaluation Process (MFEP) method, all criteria which are important factors in making considerations are given weighting. (weighting) is appropriate. Decision making using the Multi Factor Evaluation Process method is carried out subjectively by considering several factors that influence alternatives. While selecting metal, SMEs still record manually, so it takes quite a long time to make decisions. Not only that, determining the quality of aluminum metal also involves visual observations just by looking at the durability and assessing the physical metal. To overcome the problems faced by the old system. then a new system was formed, where the selection process could be carried out by Toko Berkah Qory Siregar Aluminum without waiting a long time . The results obtained based on calculations are Aluminum A, namely Blue Sky Aluminum with a preference value of 100.